Unlocking Meaning : A Semantic Analysis of Denotation and Connotation in Langton Hughes' Poetry - Rudianto, Alfina Damayanti; Andriani, Zulfi Zumala Dwi (Institut Agama Islam Negeri Palopo, 2025)
This article discusses a semantic analysis of the denotative and connotative meanings in three poems by Langston Hughes: